Nilai-Nilai Sosial di Balik “Konflik dan Kekerasan”: Kearifan Suku Sasak dalam Tradisi Mbait dan Peresean - Akhmad Asyari; Kadri (Universitas Islam Negeri (UIN) Mataram, 2022)
This study focuses to express the good social values of Sasak in two traditions that look strongly and conflict namely the tradition of mbait abducting female bride and the playing game peresean performed by striking and fending each other in the Sasak culture. The results of this qualitative study indicate that the mbait tradition which contains conflict elements which is the values of independence, seriousness, struggle, and responsibility shown by a bridegroom. The mbait tradition is followed by other customary processions such as besejati which indicate communication and reconciliation efforts as well as social harmony between two families who will marry their children. A game that looks hard also contains good social values such as courage, accuracy, honesty, sportsmanship, and brotherhood which has marked by post-battle peace. This article explicitly says that cultural rituals that contain elements of violence and conflict and do not always have negative connotations.